Edukasi Pentingnya Donor Darah melalui Media Leaflet pada Masyarakat Kunjung Mae, Kabupaten Takalar - Rahmita Rahmita; Dahniar Dahniar (Education and Talent Development Center Indonesia, 2024)
Blood donation is the process of voluntarily taking blood from someone which is stored in a blood bank for blood transfusion purposes, known as blood donation. Blood donation is an activity that really helps not only yourself but also everyone who needs it. The aim of implementing this PKM is to provide education to the public through leaflets containing information on the importance of blood donation so that the public knows the benefits of donating for themselves and others. In addition, it is very important to inform the public about the health benefits offered by blood donation so that the public is more open to voluntary blood donation. This activity was attended by 30 people from the Kunjung Mae neighborhood, Takalar Village, Mappakasunggu District, Takalar Regency. The results of this activity show that knowledge of blood donation has increased so that people in the Kunjung Mae neighborhood can participate in helping meet the need for blood in Indonesia.